Finance and Development, June 1973. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1973)
This paper reviews the influence of the tropical climate on economic development. The paper highlights that the effect of climate is clearly not the only ruling constraint on economic development. It is claimed that climatic factors severely hamper development through their impact on both human beings and their agriculture. Human economic activity is directly and adversely affected through the widespread extent and impact of diseases; and tropical agriculture suffers in the quality of its soils, its rainfall, and its multiplicity of pests and diseases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet